Analisis Kebutuhan Pengembangan E-LKPD Berbasis Liveworksheets pada Pembelajaran IPS Kelas V SD Kota Bengkulu - Devy Sefiana Putri; Badeni Badeni (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze the needs in the development of Electronic Student Worksheets (LKPD) based on liveworksheets in social studies learning in class V elementary school in Bengkulu City. The background of this study is the still use of printed LKPD which is considered less visually appealing and less encouraging student involvement and activeness in learning, resulting in a decrease in students' enthusiasm and motivation in learning. The method used is a qualitative approach with in-depth interview techniques with teachers and grade V students at SDN 45 Bengkulu City as research subjects. The results of the research from the needs analysis show that teachers need teaching media that are more interactive and relevant to the learning context, especially in Social Sciences (IPS) subjects. On the other hand, students showed interest in digital-based learning media that was more interesting and more flexible to access. Based on these findings, it can be concluded that the development of liveworksheet-based E-LKPD is an urgent need. This medium has the potential to be a solution because it offers interactive features, a more attractive visual display, and cost efficiency, while also matching the learning characteristics of elementary school students.